THE IDENTITY OF RURAL PRODUCER AND THE INFLUENTIAL CATEGORIES IN THE SUCCESSION PROCESS - Morais, Manoela; Binotto, Erlaine; Rech, Luisa Rhoden; Faustino-Dias, Álvaro Freitas; de Aguiar, Tammi Juliene Leite (Seven Editora, 2024)
The objective of this study was to identify, in the literature, the categories related to the identity of rural producers that can influence the succession process of rural properties. To this end, a systematic review of 32 scientific articles selected from the Scopus, Science Direct, and Web of Science databases was carried out. The results showed that the identity of rural producer has been related to the agricultural profile; rural tourism; gender in agriculture; health care; agricultural practices; successor identity; attachment to the land; and aging of the farmer and manifest resistance to changes in their own lives and in the property. In addition, the categories gender in agriculture, identity of successor; attachment to the land; and aging of the farmer presented more relevant elements for a rural succession process, in which the difficulties and obstacles of the process can be explained by the strong identity of rural producer present in the event. DOI: https://doi.org/10.56238/sevened2024.037-106